2000
DOI: 10.1111/1469-7610.00612
|View full text |Cite
|
Sign up to set email alerts
|

Practitioner Review: The Assessment and Treatment of Post‐traumatic Stress Disorder in Children and Adolescents

Abstract: Post-traumatic Stress Disorder (PTSD) is a syndrome defined by the intrusive reexperiencing of a trauma, avoidance of traumatic reminders, and persistent physiological arousal. PTSD is associated with high levels of comorbidity and may increase the risk for additional disorders over time. While controversies remain regarding the applicability of the PTSD criteria to very young children, it has proved to be a useful framework for guiding assessment and treatment research with older children and adolescents. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0
7

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(72 citation statements)
references
References 89 publications
1
64
0
7
Order By: Relevance
“…It is the most widely used assessment of PTSD in children (Drake, Bush & van Gorp, 2000). According to Perrin (2000), the CPTS-RI self-report measure is appropriate for use with children 8 years or older and no lower age limit has been established for the measure. As noted above, it is this author's belief that young children lack the cognitive ability to respond effectively to self-report measures, including structured interviews that children to respond through verbal means.…”
Section: Measurement Instruments Designed To Assess the Impact Of Tramentioning
confidence: 99%
“…It is the most widely used assessment of PTSD in children (Drake, Bush & van Gorp, 2000). According to Perrin (2000), the CPTS-RI self-report measure is appropriate for use with children 8 years or older and no lower age limit has been established for the measure. As noted above, it is this author's belief that young children lack the cognitive ability to respond effectively to self-report measures, including structured interviews that children to respond through verbal means.…”
Section: Measurement Instruments Designed To Assess the Impact Of Tramentioning
confidence: 99%
“…Several studies have identified a number of pre-trauma risk factors including; prior traumas [20] prior psychiatric problems [25,32,34] and family cohesion [35]. Whilst type and severity of exposure are recognised as important predictors of PTSD in adults and children, studies have reported other specific peri-trauma factors including: a strong acute trauma response [23,36,37], witnessing dead people [26], being physically injured [10] and perceived life threat [24,36,37]. Post trauma factors associated with PTSD in children include: social support [25] and co-morbidity, especially depression and generalised anxiety [38][39][40].…”
Section: The Omagh Bombingmentioning
confidence: 99%
“…Parents were coached to support and reward their Evidenced based practice in family therapy 18 children through the process of facing anxiety provoking situations while avoiding engaging in compulsive anxiety reducing rituals. Perrin, Smith, and Yule (2000) in their review of the treatment of post-traumatic stress disorders in children and adolescents concluded that there is evidence from a small number of controlled trials for the effectiveness of cognitive behavioral programs for this disorder. Such programmes begin with psychoeducation and goal setting following which youngsters are trained in coping and relaxation skills that are subsequently used in exposure sessions.…”
Section: Anxietymentioning
confidence: 99%